Sequencing and characterization of the Megachile sculpturalis (Hymenoptera: Megachilidae) mitochondrial genome. (4th May 2017) - Zhang, Yan; Su, Tianjuan; He, Bo; Gu, Ping; Huang, Dunyuan; Zhu, Chaodong
Abstract: The mitochondrial genome (mitogenome) of Megachile sculpturalis (Hymenoptera: Megachilidae) has been reported in this study. This is the first sequenced mitogenome from the family Megachilidae. The sequenced region of this mitochondrial genome is determined to be 16 581 bp in length, including 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a partial sequence of the AT-rich region, and the AT-rich region contains several characteristic repeated sequences. Additionally, we conducted a phylogenetic analysis using all the mitochondrial genomes of Apoidea that are available in Genbank. Bayesian method supported the monophyly of both Apidae and Colletidae. And Megachilidae was inferred as the sister group of Apidae.